Pengaruh Good Corporate Governance Terhadap Profitabilitas (Studi Pada Perusahaan Manufaktur Di Bursa Efek Indonesia) - Sri Oktaryani; Siti Sofiyah Abdul Mannan; I Nyoman Nugraha Ardana Putra (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
This study is aimed to determine the effect of Good Corporate Governance on profitability. Good Corporate Governance consist of three variables, which are independent commissioner, managerial ownership and institutional ownership. While profitability is measured by Return on Equity (ROE). The population of this research is manufacturing companies that listed on the Indonesia Stock Exchange. There are 43 companies as samples in this study which were obtained by purposive sampling method. Data collected by combining cross-section and time-series data. Furthermore, panel data analyze by multiple linear regression analysis by using EViews software. The findings show that independent commissioners, managerial ownership and institutional ownership has no significant effect on profitability.